Health effects of energy drinks, facts and myths - literature review - Michał Żuber; Paulina Dąbrowska; Karol Bochyński; Michał Dacka; Katarzyna Molenda; Konrad Białogłowski; Katarzyna Ciuba; Filip Borodziuk; Barbara Borodziuk; Kamila Giżewska (Kazimierz Wielki University, 2024)
Energy drinks are carbonated or non-carbonated beverages containing stimulants designed to improve energy and concentration. These drinks are gaining popularity, specifically among teenagers and young adults. However, despite their easy availability on store shelves, there is growing concern about the safety and health effects of consuming energy drinks in particular. Energy drinks appear to have the greatest impact on the cardiovascular system, leading to increased blood pressure and increased heart rate, and on the mental state of consumers, in the long term causing increased levels of anxiety. The paper also addresses the effects of energy drinks on the nervous and gastrointestinal systems. Despite many studies, the health effects of energy drinks have still not been fully investigated, so there is a need for further research on the subject and for age-appropriate regulation of consumers and their education.